Level of Haemoglobin and Knowledge Regarding Anemia and Its Prevention Among Adolescent - Desi Oktariana; Evi Lusiana; Nia Savitri Tamzil; Gita Dwi Prasasty (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Anemia is a condition in which hemoglobin (Hb) concentration being lower than a specific threshold. The prevalence of anemia among adolescents is varies among country and its proportion is higher in developing countries. In Indonesia, the proportion of anemia in the 15-24-year age group was 32%. Anemia in adolescents has a negative impact on decreased immunity, impaired physical growth and mental development, concentration, learning achievement, adolescent fitness and productivity. Knowledge of the extent and causes of anemia in adolescence is very important because it is a window of opportunity for interventions to improve adolescent health. This study aims to describe level of Hb and knowledge regarding anemia and its prevention among adolescents. This research is a descriptive study with a cross sectional method using Hb meter to assess Hb level and questionnaire to assess knowledge regarding anemia and its prevention among adolescents, conducted in November 2019. The respondents were 42 adolescents in SMPN 9 Palembang. The ages of respondents in this study ranged from 12-13 years, consisting of 36% boys and 64% girls. The mean value of Hb level in all adolescent was 13.78 g/dL with 12% of respondents had anemia. A total of 76% adolescents had poor knowledge, while 24% adolescents had good knowledge. The mean value of Hb level in all adolescent was normal, only few adolescents had anemia. This study also shows majority of the adolescents have poor knowledge about anemia and its prevention.